Functions of subventricular zone neural precursor cells in stroke recovery - Williamson, Michael R. (Behav Brain Res, 2019)
The proliferation and ectopic migration of neural precursor cells (NPCs) in response to ischemic brain injury was first reported two decades ago. Since then, studies of brain injury-induced subventricular zone cytogenesis, primarily in rodent models, have provided insight into the cellular and molecular determinants of this phenomenon and its modulation by various factors. However, despite considerable correlational evidence—and some direct evidence—to support contributions of NPCs to behavioral recovery after stroke, the causal mechanisms have not been identified. Here we discuss the subventricular zone cytogenic response and its possible roles in brain injury and disease, focusing on rodent models of stroke. Emerging evidence suggests that NPCs can modulate harmful responses and enhance reparative responses to neurologic diseases. We speculatively identify four broad functions of NPCs in the context of stroke: cell replacement, cytoprotection, remodeling of residual tissue, and immunomodulation. Thus, NPCs may have pleiotropic functions in supporting behavioral recovery after stroke.